Learning an Embodied Visual Language: Four Imitation Strategies Available to Sign Learners - Shield, Aaron; Meier, Richard P. (Frontiers in Psychology, 2018)
The parts of the body that are used to produce and perceive signed languages (the hands, face, and visual system) differ from those used to produce and perceive spoken languages (the vocal tract and auditory system). In this paper we address two factors that have important consequences for sign language acquisition. First, there are three types of lexical signs: one-handed, two-handed symmetrical, and two-handed asymmetrical. Natural variation in hand dominance in the population leads to varied input to children learning sign. Children must learn that signs are not specified for the right or left hand but for dominant and non-dominant. Second, we posit that children have at least four imitation strategies available for imitating signs: anatomical (Activate the same muscles as the sign model), which could lead learners to inappropriately use their non-dominant hand; mirroring (Produce a mirror image of the modeled sign), which could lead learners to produce lateral movement reversal errors or to use the non-dominant hand; visual matching (Reproduce what you see from your perspective), which could lead learners to produce inward–outward movement and palm orientation reversals; and reversing (Reproduce what the sign model would see from his/her perspective). This last strategy is the only one that always yields correct phonological forms in signed languages. To test our hypotheses, we turn to evidence from typical and atypical hearing and deaf children as well as from typical adults; the data come from studies of both sign acquisition and gesture imitation. Specifically, we posit that all children initially use a visual matching strategy but typical children switch to a mirroring strategy sometime in the second year of life; typical adults tend to use a mirroring strategy in learning signs and imitating gestures. By contrast, children and adults with autism spectrum disorder (ASD) appear to use the visual matching strategy well into childhood or even adulthood. Finally, we present evidence that sign language exposure changes how adults imitate gestures, switching from a mirroring strategy to the correct reversal strategy. These four strategies for imitation do not exist in speech and as such constitute a unique problem for research in language acquisition.